2.1 Estimation of detection rates of aneuploidy using an approach based on nuchal translucency and non-invasive prenatal testing (NIPT). (9th June 2014) - Khalil, A; Mahmoodian, N; Kulkarni, A; Homfray, T; Papageorghiou, A; Bhide, A; Thilaganathan, B
Abstract : Objectives: To investigate the detection rates of aneuploidy using nuchal translucency (NT) and non-invasive prenatal testing (NIPT). Methods: A retrospective cohort study including 5306 pregnancies that underwent chorionic villus sampling (CVS) for full karyotyping after fetal NT measurement at 11+0–13+6 weeks of gestation. All abnormal karyotypes were reviewed by a clinical geneticist and grouped according to whether the chromosome anomaly would be detectable by NIPT and whether it might be clinically significant. Results: The fetal karyotype was normal in 4172 (78.6%) and abnormal in 1134 (21.4%), including 1009 likely to result in clinically significant adverse outcome. Universal CVS with full karyotyping would lead to the diagnosis of all clinically significant abnormalities. A policy of NIPT only in all of these cases would have led to the diagnosis of 88.9% of clinically significant abnormalities. A strategy whereby NIPT is the main method of analysis for increased combined screening risk, with invasive testing reserved for those with NT thickness ≥3.0 mm, would require CVS in 20.1%, identify 94.8% of significant abnormalities and avoid miscarriage in 42 (79.2%) pregnancies compared to CVS for all. With a current UK price for NIPT of £400 and the need to confirm abnormal results by CVS, the cost of the three policies would be £2.0 m, £2.5 m and £2.2 m, respectively. Conclusions: A policy of NIPT for increased first trimester aneuploidy risk and CVS with full karyotype only for fetal NT thickness ≥3.0 mm would reduce the risk of procedure-related miscarriage five-fold, yet identify 95% of clinically significant chromosomal abnormalities.